Why hierarchy? Communication and information acquisition in organizations - Junichiro Ishida (Osaka University, Institute of Social and Economic Research (ISER), 2009)
In most firms, if not all, workers are divided asymmetrically in terms of authority and responsibility. In this paper, we view the asymmetric allocations of authority and responsibility as essential features of hierarchy and examine why hierarchies often prevail in organizations from that perspective. The focus of attention is on the tradeoff between costly information acquisition and costless communication. When the agency problem concerning information acquisition is sufficiently severe, the contractual arrangement which allocates responsibility asymmetrically often emerges as the optimal organizational form, which gives rise to the chain of command pertaining to hierarchical organizations. This explains why hierarchies often prevail in firms since a relatively fixed group of members must confront with new problems and come up with solutions on the day-to-day basis, and hence the agency problem is an issue to be reckoned with.
Keywords: D03; D99; 330; Authority; Responsibility; Contract; Communication; Cheap talk; Information acquisition